Evaluation of growth and the floral morphology and the fruit of chilacuán (Vasconcellea cundinamarcensis B.) - Meza, Stefani David; Osorio Guerrero, Karen Viviana; Lagos Burbano, Tulio César (Revista de Ciencias Agrícolas, 2011)
This work was performed under conditions of the Altiplano de Pasto, Colombia, in the garden conservation of Chilacuán V. cundinamarcensis, located at the Experimental Farm Botana at 2800 masl. The objectives focused on the description and analysis of some stages of flower development and fruit, as well as evaluation of aspects related to growth and morphology of these. We selected 300 male and female flower buds less than 8 mm, as phase zero. The growth variables were length of calyx, calyx diameter, and length of corolla, diameter of corolla, length of the pistil, diameter of pistil, length of ovary, ovarian diameter, length of the filament and style, length and width of anthers, length and equatorial diameter fruit. These were-evaluated every 15 days to 210 days, at which time the fruits reached their peak maturity (11 °Brix). Likewise, the viability of pollen and pistil receptivity in various stages of testing was studying. From zero state (8 mm), the pistil is receptive at 30 days and the pollen grain is viable at 45 days. Also record the fruit growth and behavior of the variable content of pulp/fruit, seeds/fruit, juice yield, hardness and color of the ripe fruit. The growth of quantitative variables were adjusted to a quadratic model of the form y= P1x+P2x2.